Exploring Blockchain Technology for Transparency and Efficiency in Indonesia's Financial Sector - Suyanto, Suyanto; ASTUTI, INDRI; Duryana, Duryana (PT. Anagata Sembagi Education, 2024)
The application of blockchain technology in Indonesia's financial sector offers great potential to improve the transparency, efficiency, and security of the financial system. Blockchain allows for permanent and transparent recording of transactions, thereby reducing the risk of fraud and data manipulation, as well as increasing public trust in the financial system. The technology also has the potential to reduce international transaction costs, speed up payment processes, and reduce reliance on intermediaries, allowing financial services to become more affordable and efficient. However, Indonesia faces various challenges in implementing blockchain, including regulatory clarity that risks creating legal uncertainty, limited digital infrastructure that is evenly distributed across the region, and a lack of skilled human resources in this technology. To overcome these challenges, collaboration between governments, regulators, and the private sector is needed to create policies that support blockchain development, strengthen digital infrastructure, and improve the quality of education and training in the field of blockchain technology. The great potential of blockchain in accelerating the transformation of Indonesia's financial sector towards a more inclusive, efficient, and transparent system will be the main driver of sustainable digital economic growth.